2020
DOI: 10.1080/22221751.2020.1737579
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of Helicobacter pylori reinfection and its risk factors after initial eradication: a large-scale multicentre, prospective open cohort, observational study

Abstract: Helicobacter pylori (H. pylori) recurrence remains a significant public health concern. The study aimed to assess H. pylori reinfection rate and identify its risk factors in China. This prospective open cohort, observational study was performed at 18 hospitals across 15 provinces in China. Consecutive patients who received the successful initial eradication during 1 January 2012 and 31 December 2018 were eligible for enrolment. H. pylori recurrence was defined as reinfection that occurred at more than the 12-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 43 publications
2
33
1
Order By: Relevance
“…The recurrence rate in the present study was a little higher than that reported previously, which may be caused by many factors, such as location, economic level, scheme selection, drug compliance, and detection method. The latest multicenter prospective study has suggested that ethnic groups, education level, family history, and residence location are independent risk factors for H. pylori recurrence Gastroenterology Research and Practice [26]. The authors found that the recurrence rate of the residence located in Western China was significantly higher than that of other places, which may partially explain the high recurrence rate of H. pylori infection in the present study, since Chongqing is a western city in China.…”
Section: Discussionsupporting
confidence: 45%
“…The recurrence rate in the present study was a little higher than that reported previously, which may be caused by many factors, such as location, economic level, scheme selection, drug compliance, and detection method. The latest multicenter prospective study has suggested that ethnic groups, education level, family history, and residence location are independent risk factors for H. pylori recurrence Gastroenterology Research and Practice [26]. The authors found that the recurrence rate of the residence located in Western China was significantly higher than that of other places, which may partially explain the high recurrence rate of H. pylori infection in the present study, since Chongqing is a western city in China.…”
Section: Discussionsupporting
confidence: 45%
“…In a large cohort from South Korea (10 468 eradicated subjects), reinfection of H pylori was calculated to occur at the rate of 3.06% per person‐year 28 . In a multi‐centre prospective, observational study in China involving 5193 subjects, the annual reinfection rate was 1.5% 29 . Reinfection was associated with the following risk factors: minority groups (HR = 4.7, 95% CI, 1.6‐13.9), a low level of education (HR = 1.7, 95% CI, 1.1‐2.6), a family history of gastric cancer (HR = 9.9, 95% CI, 6.6‐14.7), and the residence located in Western China (HR = 5.5, 95% CI, 2.6‐11.5) following by Central China (HR = 4.9, 95% CI, 3‐8.1) (all P < .05) 29 …”
Section: Reinfectionmentioning
confidence: 99%
“…It is also associated with mucosa-associated lymphoid tissue (MALT) lymphoma, although the transmission pattern of this pathogen is not completely understood [ 25 , 26 ]. Overall, it is widely known that H. pylori is transmitted through oral-oral, fecal-oral, and gastro-oral routes [ 27 ]. As a highly prevalent infection, H. pylori is commonly acquired in early stages of life and grows in digestive tract and stays in the host’s body for the rest of its life [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%